2010
DOI: 10.1007/s11136-010-9685-6
|View full text |Cite
|
Sign up to set email alerts
|

Measuring community integration after spinal cord injury: validation of the Sydney psychosocial reintegration scale and community integration measure

Abstract: Research should continue to develop conceptually and psychometrically valid instruments to capture the multidimensionality of community integration. The SPRS and CIM show potential to extend measurement of community reintegration following SCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 24 publications
2
11
0
2
Order By: Relevance
“…Our results showed that the overall level of community integration (mean (SD): 43.48 (5.79)) was comparable to those reported among people with spinal cord injury (SCI) [18] (mean (SD): 42.50 (5.80)) but higher than those of people with traumatic brain injury (TBI) (mean (SD): 39.40 (8.10)) [14] and acquired brain injury (ABI) (mean (SD): 28.80 (7.70)) [13]. The study found that people with stroke, like those with SCI, have a high level of community integration as measured by the CIM.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Our results showed that the overall level of community integration (mean (SD): 43.48 (5.79)) was comparable to those reported among people with spinal cord injury (SCI) [18] (mean (SD): 42.50 (5.80)) but higher than those of people with traumatic brain injury (TBI) (mean (SD): 39.40 (8.10)) [14] and acquired brain injury (ABI) (mean (SD): 28.80 (7.70)) [13]. The study found that people with stroke, like those with SCI, have a high level of community integration as measured by the CIM.…”
Section: Discussionsupporting
confidence: 78%
“…55 percent of our subjects claimed to exercise 7 times per week, and this group of patients would be more active to join the community activities. In De Wolf's study [18], 60% of the subjects with SCI had a low impairment levels (tetraplegia ASIA D or paraplegia), and all the subjects in our present study had high level of functional mobility. In addition, the functional mobility of our subjects with stroke, similar to those of patients with SCI, can mostly be compensated for by efficient use of assistive devices, walking aids, and/or a wheelchair.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Second, for the SCI sample, item 10 (personal habits) was answered from the perspective of whether or not the participant was able to complete self‐care tasks either independently or by directing attendant carers; whereas in the TBI and PBT samples, item 10 was rated strictly in terms of whether the person was able to complete the task independent of another person's involvement, whether for direct care, supervision, or prompt. The SPRS (and its revision, SPRS‐2) has been extensively validated with TBI populations (Tate et al., 1999, 2011) and more recently for the SCI population (De Wolf, Lane‐Brown, Tate, Middleton, & Cameron, 2010). However, it has not previously been examined psychometrically for people with PBT.…”
Section: Methodsmentioning
confidence: 99%